2D Crystals Significantly Enhance the Performance of a Working Fuel Cell. Issue 5 (3rd November 2016) - Holmes, Stuart M.; Balakrishnan, Prabhuraj; Kalangi, Vasu. S.; Zhang, Xiang; Lozada‐Hidalgo, Marcelo; Ajayan, Pulickel M.; Nair, Rahul R.
Abstract : 2D atomic crystals such as single layer graphene (SLG) and hexagonal boron nitride (hBN) have been shown to be "unexpectedly permeable" to hydrogen ions under ambient conditions with the proton conductivity rising exponentially with temperature. Here, the first successful addition of SLG made by a chemical vapor deposition (CVD) method is shown to an operational direct methanol fuel cell significantly enhancing the performance of the cell once the temperature is raised above 60 °C, the temperature at which the proton conductivity of SLG is higher than the Nafion membrane on which it is mounted. Above this temperature, the resistance to proton transport of the system is not affected by the graphene but the barrier properties of graphene inhibit methanol crossover. The performance of the fuel cell is shown to increase linearly with coverage of SLG above this temperature. Results show that the maximum power density is increased at 70 °C by 45% in comparison to the standard membrane electrode assembly without graphene. In addition, a membrane with CVD hBN shows enhanced performance across the entire temperature range due to better proton conductivity at lower temperatures. Abstract : Single layer graphene (above 50 °C) and hexagonal boron nitride (at all temperatures) have very high proton conductivity but zero permeability to all other species. As such they act as an effective barrier to fuel crossover in a working direct methanol fuel cell, enhancing the power density of the system.